South Florida ornamental plant grower perspectives: water conservation management practices - Kati W. Migliaccio; Edward Evans; Jonathan H. Crane; Bruce Schaffer; Yuncong Li; Rafael Muñoz-Carpena (EDIS)
ABE-369, a 5-page fact sheet by Kati W. Migliaccio, Edward Evans, Jonathan H. Crane, Bruce Schaffer, Yuncong Li, and Rafael Muñoz -Carpena, presents the results of a survey designed to assess changing views of ornamental plant producers in Miami-Dade County regarding water quantity and quality management practices. Published by the UF Department of Agricultural and Biological Engineering, July 2006.